Perinatal factors and early neonatal outcomes of abnormal birthweight infants in Hangzhou, China, 2015-2021: a retrospective cohort study - Yan Jiang; Yiming Chen; Yanan Wang; Huimin Zhang; Lingling Huang; Wenwen Ning; Xuelian Chu (BMJ Publishing Group, 2024)
Background This study aimed to investigate the perinatal factors and early neonatal outcomes of abnormal birth weight (ABW) in Hangzhou, China from 2015 to 2021.Methods A retrospective cohort study was designed to analyse the data of 76 847 newborns, in which the case groups included 3042 cases of low birth weight (LBW) and 2941 cases of fetal macrosomia (MAC), and 70 864 cases of normal weight were as the reference group.Results The incidence of LBW and MAC was 3.96% and 3.83% in Hangzhou, China from 2015 to 2021. Prematurity (<37 weeks), multiple births, hospitalisation >7 days, fetal anomalies, caesarean section, pregnancy complications, maternal coinfection with pathogens and summer births would be correlated with the incidence of LBW (ORs=43.50, 7.60, 2.09, 1.89, 1.57, 1.28, 1.19 and 1.18, all p<0.05). Factors such as post-term pregnancy (>41 weeks), scarred uterus, anterior vaginal incision and gravidity ≥2 were correlated with decreased incidence of LBW, with ORs of 0.05, 0.54, 0.65 and 0.80. Moreover, caesarean delivery, post-term pregnancy (> 41 weeks), parity ≥1, lateral vaginal incision, gravidity ≥2, hospitalisation >7 days, winter births and pregnancy complications also have association with the incidence of MAC (ORs=3.92, 2.73, 2.19, 1.87, 1.22, 1.20, 1.17 and 1.13, all p<0.05) while prematurity (<37 weeks), scarred uterus and anterior vaginal incision have close association with decreased incidence of MAC, with ORs of 0.07, 0.21 and 0.74 (all p<0.05).Conclusion There was a trend of yearly increase in ABW in Hangzhou, China from 2015 to 2021. Several neonatal and maternal-related variables such as caesarean section, pregnancy complications and hospitalisation >7 days are associated with the odds of LBW and MAC, however, factors such as pregnancy with scarred uterus relate to the decrease of ABW. Close monitoring and intervention during pregnancy are essential to reduce the occurrence of ABW.